Biochemical studies on the reverse transcriptase and RNase H activities from human immunodeficiency virus strains resistant to 3'-azido-3'-deoxythymidine - Lacey, S F; Reardon, J E; Furfine, E S; Kunkel, T A; Bebenek, K; Eckert, K A; Kemp, S D; Larder, B A (The Journal of biological chemistry, 1992)
A series of biochemical investigations to compare the DNA polymerase and RNase H functions of the reverse transcriptases (RTs) corresponding to azidothymidine (AZT)-sensitive and -resistant human immunodeficiency virus (HIV) strains are described. Steady-state kinetic studies with purified recombinant enzymes utilizing several templates and three inhibitors, 3' azido-3' deoxythymidine triphosphate (AZTTP), 3-amino-thymidine 5'-triphosphate, and 2',3'-didehydro-2',3'-dideoxythymidine 5'-triphosphate, found consistent 2-4-fold differences between the enzymes from the two strains over a wide pH range. A strong pH dependence for all three inhibitors was found at pH values below 7.4 and suggested an ionizable group on the enzyme with a pK of about 7. The sensitivities of the RNase H activities of the two enzymes to AZTTP and AZTMP were also compared and found to be similar. The nucleotide incorporation fidelities of recombinant RTs corresponding to AZT-sensitive and -resistant clinical isolates were compared and the error specificities determined. No significant differences were found. Both enzymes were equally able to incorporate AZTTP into an elongating M13 DNA strand with concomitant chain termination. Purified wild-type and mutant virions from cell-culture supernatants were compared in "endogenous" DNA synthesis reactions, and the sensitivities of this activity to AZTTP were found to be similar. The contrast between the small differences found in this study and the high level of viral resistance in tissue culture presumably reflects an incomplete understanding of AZT inhibition of HIV in the cell.